Penguatan Moderasi Beragama Dalam Program Ta’lim Al-Afkar Maha Santri Ma'had Al-Jami'ah IAIN Pontianak - Siti Fatimah; Hermansyah; Erwin Mahrus; Muh Idris; Ainur Alam Budi Utomo (Kartika: Jurnal Studi Keislaman, 2026)
Religious moderation is an important principle in maintaining harmony within Indonesia’s pluralistic society. Islamic higher education institutions, particularly through the Ma’had Al-Jami’ah system, play a strategic role in instilling these values among students. This study aims to analyze the impact of the Ta‘lim al-Afkar program on the understanding and attitudes of religious moderation among maha santri at Ma’had Al-Jami’ah IAIN Pontianak. The research employs a mixed-method approach with an integrative quantitative and qualitative design. Quantitative data were collected through questionnaires, while qualitative data were obtained through interviews and observations. The results indicate that the level of understanding and attitudes toward religious moderation is in the very high category, with an average percentage of 87.96%. The tolerance indicator reached 91.4%, comprehensive understanding of moderation 92.2%, national commitment 89.8%, and accommodation of local traditions 87.5%, while the anti-violence indicator was in the high category at 78.9%. Qualitative findings reveal that the program not only enhances cognitive understanding but also fosters reflective awareness and practical readiness in applying moderate attitudes in both academic and social life